Периоперационная респираторная поддержка и послеоперационные исходы: российское национальное эпидемиологическое исследование «РуВент-А»: протокол исследования - Ярошецкий, Андрей Игоревич; Трембач, Н. В.; Парванян, С. Г.; Кузьков, В. В.; Мазурок, В. А.; Грицан, А. И.; Власенко, А. В.; Еременко, А. А.; Комнов, Р. Д.; Заболотских, И. Б. (Vestnik intensivnoĭ terapii, 2025)
INTRODUCTION: Annually, approximately 230 million patients undergo general anesthesia and mechanical ventilation, which is associated with a high incidence of postoperative pulmonary complications (PPC). Despite the proven efficacy of protective ventilation, the actual respiratory support strategies in Russian operating rooms remain insufficiently studied, underscoring the relevance of the RuVent-A study. MATERIALS AND METHODS: In the multicenter observational study RuVent-A, data will be collected using specialized electronic forms (Center Card and Patient Protocol) integrated into a secure web platform that ensures anonymization, regular backup, and quality control of the data. onditions: This is a multicenter observational study of patients undergoing surgical interventions under mechanical ventilation. Patients: The study includes all patients over 18 years of age undergoing surgical interventions under general anesthesia over a period of 5 working days. Interventions: The study records respiratory support parameters (tidal volume, PEEP, FiO₂, ventilation modes, etc.), the type of surgical intervention, comorbidities, and the subsequent occurrence of PPC, while no changes to clinical protocols are made. RESULTS: The developed study design has been registered in the ClinicalTrials.gov database, confirming its compliance with international standards and ensuring the transparency of the research. CONCLUSIONS: It is anticipated that the results of RuVent-A will help identify current respiratory support strategies, determine key risk factors for PPC, and formulate recommendations for optimizing perioperative ventilation in Russia, ultimately enhancing the quality of medical care and patient safety. АКТУАЛЬНОСТЬ: Ежегодно в мире около 230 миллионов пациентов подвергаются общей анестезии и искусственной вентиляции легких, что сопровождается высоким уровнем послеоперационных легочных осложнений (ПОЛО). Несмотря на доказанную эффективность протективной вентиляции, реальные стратегии респираторной поддержки в операционных РФ остаются недостаточно изученными, что определяет актуальность исследования RuVent-A. МАТЕРИАЛЫ И МЕТОДЫ: В многоцентровом обсервационном исследовании RuVent-A планируется сбор данных посредством специализированных электронных форм (Карточка центра и Протокол пациента), интегрированных в защищенную веб-платформу, обеспечивающую анонимизацию, резервное копирование и контроль качества данных. Условия: многоцентровое наблюдательное исследование пациентов, подвергающихся оперативным вмешательствам в условиях ИВЛ. Пациенты: в исследование включаются все пациенты старше 18 лет, которым проводится оперативное вмешательство под общей анестезией в течение 5 рабочих дней. Вмешательства: в рамках исследования фиксируются параметры респираторной поддержки (дыхательный объем, PEEP, FiO₂, режимы вентиляции и прочее), тип оперативного вмешательства, сопутствующие заболевания и последующее возникновение ПОЛО, при этом изменение клинических протоколов не производится. РЕЗУЛЬТАТЫ: Разработанный дизайн был зарегистрирован в базе данных ClinicalTrials.gov, что подтверждает его соответствие международным стандартам и обеспечивает прозрачность исследования. ВЫВОДЫ: Ожидается, что результаты RuVent-A позволят выявить актуальные стратегии респираторной поддержки, определить ключевые факторы риска ПОЛО и сформировать рекомендации для оптимизации периоперационной вентиляции в РФ, что в перспективе повысит качество медицинской помощи и безопасность пациентов.